Pengaruh Latihan Aerobik Low Impact Terhadap Tingkat Stres Ibu - Amalina, Ayu; Priasmoro, Dian Pitaloka; Murtadho, Maulana Arif (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: The study aims to examine the effect of low-impact aerobic exercise on stress levels among mothers in the Sumbertaman area, Probolinggo City.. Methods:. This research used a pre-experimental design with a one-group pretest-posttest approach. The population consisted of 35 PKK mothers who took the pre-test to post-test who met the results criteria. Data was collected using the Perceived Stress Scale (PSS) questionnaire which was carried out in November 2024. The intervention was carried out three times a week with a focus on low-impact aerobic exercise. Data analysis was carried out using univariate descriptive analysis and the Wilcoxon Signed Rank Test.. Results: The Wilcoxon test results showed a sig value (2-tailed) p = 0.001 < 0.05, there was a significant reduction in stress levels after the intervention. Pre-test data shows that 50% of respondents experience high stress, while post-test results show that only 10% are still in the high stress category. The Wilcoxon test shows the significant effectiveness of low impact aerobic exercise in reducing stress levels. Conclusion: Low-impact aerobic exercise effectively reduces stress levels among PKK mothers in Sumbertaman. This exercise can be recommended as an accessible and practical method for improving mental health and well-being in community settings.